A Death Squad Dossier: Counterrevolutionary Policing, Photographs of Disappearing Identities and Evidentiary Aesthetics in Postwar Guatemala. Issue 3 (2nd October 2021) - Mazariegos, Juan Carlos
Abstract : This article is concerned with photographic images and identity photographs utilised for military counterinsurgent policing in Guatemala City during the civil war (1960–96), in the context of Latin America's Cold War. The article explores the historical conditions that made militarised policing and its photographic record possible in Guatemala, focusing on a dossier produced in the early 1980s known as Diario Militar . The article pays attention to aesthetic and evidentiary regimes that rely on the indexical force of photographs under circumstances in which indexicality fails. In doing so, it elaborates on counterrevolutionary policing as a way of seeing and not being seen, producing photographic images that at once identify political subjects and attempt to disappear their identities, and how these photographic imaginaries are being re-signified in contemporary struggles for justice in postwar Guatemala.